The 2nd International Research Conference on Sustainable Energy, Engineering, Materials and Environment 2018
DOI: 10.3390/proceedings2231487
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Multiple Parameters on Energy Performance of PV-DSF Buildings

Abstract: Double Skin Façade (DSF) has been widely used in buildings to enhance energy efficiency and bring daylight and aesthetic benefits. Solar photovoltaic (PV) modules can be integrated in DSF to fully or partially meet the electricity demand. Therefore, in this study, the energy performance of a 3-storey PV-DSF building is analyzed for three cities of Iran with distinctive climates namely Tehran, Tabriz and Kish Island considering different orientations, cavity widths and different optical properties for the PV sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…The building three‐dimensional model is also shown in Figure . As depicted in Figure , the findings of this study are in good agreement with that of the previous study …”
Section: Methodssupporting
confidence: 92%
See 1 more Smart Citation
“…The building three‐dimensional model is also shown in Figure . As depicted in Figure , the findings of this study are in good agreement with that of the previous study …”
Section: Methodssupporting
confidence: 92%
“…To assess the validity of results, a simple three‐story office building as presented in a selected article is simulated in DesignBuilder. BIPV windows are used in the building and the properties of PV are summarized in Table .…”
Section: Methodsmentioning
confidence: 99%
“…The thermal and energy performance of DSF buildings are influenced by some parameters such as building orientation, glazing type, cavity width, and climatic conditions, as well as by the use of photovoltaic cells, phase change materials or venetian blinds, and by air ventilation mode option [13][14][15][16][17][18]. Proper DSF integration with PCM leads to up to 10.38% of building energy savings [13].…”
Section: Introductionmentioning
confidence: 99%
“…Proper DSF integration with PCM leads to up to 10.38% of building energy savings [13]. In the work of Fazelpour et al [14], it was found that with the increase in cavity width from 0.4 to 1.2 m, the annual electricity consumption is reduced by 5.88, 5.19, and 7.49 MWh for Tehran, Tabriz, and Kish, respectively. When the slat angle is adjusted from 0 • to 90 • the temperature of the inner glazing reduces 1 • C at least [16].…”
Section: Introductionmentioning
confidence: 99%
“…The DSF thermal and energy performance are induced by building orientation, glazing type, cavity width and climatic conditions; by the application of photovoltaic cells, phase change materials or Venetian-type blinds; and by the option of an air ventilation strategy [13][14][15][16][17][18]. The application of adequate control strategies for DSFs with internal incorporated blinds can contribute to diminish the building energy consumption and thermal loads, as shown in the work of Kim et al [19].…”
Section: Introductionmentioning
confidence: 99%